Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ© Ø¹Ù† ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ Ø¶ÙˆØ¡ Ø§Ù„Ø£ØºÙ†ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Wari ono; Muhammad Taufiq (Al-Fakkaar, 2023)
The purpose of this study was to analyze Arabic language learning at MTsN Tebing Tinggi by using Arabic songs as media. to see how the teaching and learning process is going on in the MTsN Tebing Tinggi in detail.This study uses an analytical study method with a qualitative approach, with qualitative methods enabling researchers to collect data through observation, interviews, and researcher documentation to understand social phenomena in complex and deep contexts. The results of the researchers' observations that learning to use Arabic songs is very significant in increasing vocabulary mastery, making children more active, and student participation in the application of singing methods and Arabic songs. To establish active communication between students. In addition, communication between teachers and students seems effective and intimate. Through the application of the singing method, students' mastery of Arabic vocabulary is improved. With the wider vocabulary or mufradat, students' speaking ability will also increase. It can be concluded that the use of Arabic song-based media at MTsN Tebing Tinggi goes well and smoothly, it also has a positive impact on increasing students' mastery of Arabic at MTsN Tebing Tinggi